1977
DOI: 10.1002/jez.1402020108
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenic distribution of limb regeneration capacity in adult Amphibia

Abstract: Limb regeneration was studied in 13 adult amphibian species in which regeneration had not previously been investigated. Limb regeneration was not exhibited by four anuran species: Pseudacris triseriata, Hyla squirilla, Hyla crucifer, and Bufo quercicus. Among the adult urodeles studied, normal regeneration was observed in five species: Ambystoma laterale, another Ambystoma jeffersonianum complex species, Eurycea bislineata, Plethodon cinereus, and Plethodon glutinosus. Limb regeneration was absent or heteromor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
60
1

Year Published

1983
1983
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 22 publications
1
60
1
Order By: Relevance
“…Maintaining the salamander in an aquatic environment stimulates, to some extent, the breeding state whereby the salamander does not eat and essentially starves to death. The results in this report as well as those of Scadding (1977) support this idea. An additional consideration is that the salamanders are nocturnal in their activities, both in pursuit of their food source and in other ancillary activities.…”
Section: Aquaticsupporting
confidence: 93%
See 4 more Smart Citations
“…Maintaining the salamander in an aquatic environment stimulates, to some extent, the breeding state whereby the salamander does not eat and essentially starves to death. The results in this report as well as those of Scadding (1977) support this idea. An additional consideration is that the salamanders are nocturnal in their activities, both in pursuit of their food source and in other ancillary activities.…”
Section: Aquaticsupporting
confidence: 93%
“…The above results show that 1) postmetamorphic adult land-phase salamanders can survive under appropriate laboratory conditions for extended periods of time; 2) adult Scadding (1977) found that environmental conditions optimal for regeneration in the aquatic-phase urodeles (i.e., aquatic habitat with fresh liver as a food source) produced either heteromorphic or nonexistent regeneration (and death) in land-phase urodeles after a 60-day observation period. Our studies, as shown in Table 2, confirm this finding in that conditions for regeneration in aquatic species are detrimental to land-based species.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations